2019
DOI: 10.1002/ajcp.12399
|View full text |Cite
|
Sign up to set email alerts
|

Continuum between Relational and Therapeutic Models of Self‐help in Mental Health: A Qualitative Approach

Abstract: Highlights• Proximity between services and groups may influence the self-help methodology.• By means of a qualitative study we tried to highlight the deep meaning of self-help for members.• Through analyzing qualitative data and organizational characteristics of the groups, two sub-cultures emerged.• Suggestions emerged for services and professionals on how to support groups eliciting no distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The frequency was established for the core component and the benefits, according to the studies that cite it considering the new consolidation. The work of Petrini et al (2020) is the one that reports the most benefits, being social functioning and health learning the ones that it recognizes. Yip (2002) identifies four benefits where skills for life is the most frequent.…”
Section: Social Networkmentioning
confidence: 99%
“…The frequency was established for the core component and the benefits, according to the studies that cite it considering the new consolidation. The work of Petrini et al (2020) is the one that reports the most benefits, being social functioning and health learning the ones that it recognizes. Yip (2002) identifies four benefits where skills for life is the most frequent.…”
Section: Social Networkmentioning
confidence: 99%
“…An overview of the influence of self-help groups on family caregivers showed that self-help groups can improve caregivers’ health and psycho-physical wellbeing, and can reinforce their sense of social support [ 11 ]. The participants reported some benefits that are specific to these non-professional groups such as friendship, mutual support, a sense of belonging, and experiential knowledge [ 25 , 53 ]. Corlito [ 54 ] argued that the group fosters change through a sense of belonging, emotional sharing, and social comparison.…”
Section: Discussionmentioning
confidence: 99%
“…According to the article, the degree of utilization of experiential knowledge compared to external sources of group dependence is an important criterion for categorizing SH/MAGs. In this context, this paper also makes a decisive contribution to the delineation of SH/MAGs in relation to professionally led groups, an issue that still leads to confusion in the field today, as professionally led groups are often called SH/MAGS (Matzat, 1993; Petrini et al, 2020; Salem et al, 2008).…”
Section: Defining Self‐help/mutual Help Groupsmentioning
confidence: 99%
“…A recent article published in AJCP that discusses issues related to the definition of SH/MAGs and the delineation of their relationship with professionals is Petrini et al (2020). This qualitative research aims to understand how the support of SH/MAGs in Italy by professionals can influence both the organizational choices of the groups and the beliefs of the members.…”
Section: Relationship Of Self‐help/mutual Help Groups With Health Pra...mentioning
confidence: 99%